Automação do cálculo de vigas mistas semi-contínuas incluindo ligações mistas - Vanessa Heckert Sevilla Pires (2003)
Composite systems of semi-continous beams interconnected by composite connections are analized. With an adequate connection between the steel section and the slab, it is possible to make them work together, even in the support region. The use of steel bars within this region provides resistance to flexural moment, which also warrantsthe ductility of the whole system. For a correct design of the composite connection, a detailed study of its components is necessary, which requires complex calculations. Basicaly, resistance, stiffness and rotation capacity of all the components have to be studied. Because of that, a software was developed in Delphi language, with the objective of designing a line of beams. Rigid-plastic analisys is used for ultimate limit states and elastic analisys for the serviceability limit state. The elastic analisys is performed introducing rotational springs between the beams, with the stiffness of the composite connection. A detaileddesign of a composite floor with composite connections is presented, and the results are compared with those obtained from the developed software.